TRACES OF BLACK FREEDOM IN THE MACHINE: ETHNOGRAPHIC APPROACHES TO THE STUDY OF DIGITAL BLACK RELIGION - Gault, Erika (AoIR Selected Papers of Internet Research, 2021)
There was a time when one wanted to learn about Black religion you went to church, the Black Church to be more specific. The “all-in-one agency” which W.E. B. DuBois described the Black Church as certainly operated as a centralized and essential aspect of Black life. Its networks have come to signify Black believers’ emancipatory visions since its beginning during slavery in America. Today Black users’ contemporary engagement with digital technology has both broadened and complicated the scholarly understanding of the Black Church and Black religion to include more than its Christian manifestation. A number of works provide important theoretical and methodological approaches to the study of black digital use, digital structures of inequality, and counter-discourse production. On the topic of digital religion, works have emphasized the importance of digital technology in mediating religious experience. Yet, despite findings that people of African descent are often early adopters of technology, at the intersections of blackness, religion, and digital technology scholarly work remains sparse. This paper provides both a survey and framework for the study of digital Black religion. The work of Black religious media scholars is paired with that of Heidi Campbell and others writing on digital religion to offer a needed approach to the articulation and study of digital Black religion as a tradition rooted in notions of freedom.